Pengalaman Pasien Gagal Ginjal Kronik yang Menjalani Hemodialisa tentang Self Care, Adaptasi Diet dan Cairan - Hasan Hasan; Mulyati Mulyati; Dedi Supriadi; Iin Inayah; Susilawati Susilawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to find meaning from the experience of chronic kidney disease patients undergoing hemodialysis regarding their diet and fluid regimen so that a design for education is formed. The research method used is a qualitative research method with a phenomenological approach. The results of the study identified seven themes, namely; 1) Changes in the patient's physiological condition; 2) Expression of feelings about changes in health conditions; 3) Needs for support; 4) Changes in fulfilling dietary needs; 5) Changes in fulfilling fluid needs; 6) Needs to obtain information about treatment; 7) Barriers in following diet and fluids. In conclusion, this study recommends that patients increase their knowledge and information regarding adherence to diet and fluids. Keywords: Adaptation, Fluids, Diet, Hemodialysis Experience, Self Care